2019
DOI: 10.1124/dmd.118.084053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epacadostat on Brain Extracellular Fluid Concentrations of Serotonin—an Intracerebral Microdialysis Study in Sprague-Dawley Rats

Abstract: Epacadostat (EPAC) is an indoleamine 2,3-dioxygenase 1 (IDO1) inhibitor that has been examined in multiple clinical trials. The substrate for IDO1 is tryptophan and there is a theoretical concern that inhibition of IDO1 may increase the concentrations of tryptophan and subsequently serotonin, potentially leading to serotonin syndrome (SS). The objective of this study was to evaluate the effect of EPAC, either alone or with linezolid, a monoamine oxidase inhibitor (MAOI), on brain extracellular fluid (ECF) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The decrease of 5-HT level in peripheral blood can indirectly reflect the level of 5-HT, which may be closely related to indoleamine 2,3-dioxygenase 1 (IDO1) and metabolism of tryptophan. 39 Our results demonstrated that the level of 5-HT in serum of MDD patients was significantly decreased, and the ReHo in BA11 and BA9 regions of PFC was decreased, which was consistent with the reported study. 40 Second, we found that serum 5-HT level and ReHo value of BA11 and BA9 were negatively correlated with HAMD and SDS score.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease of 5-HT level in peripheral blood can indirectly reflect the level of 5-HT, which may be closely related to indoleamine 2,3-dioxygenase 1 (IDO1) and metabolism of tryptophan. 39 Our results demonstrated that the level of 5-HT in serum of MDD patients was significantly decreased, and the ReHo in BA11 and BA9 regions of PFC was decreased, which was consistent with the reported study. 40 Second, we found that serum 5-HT level and ReHo value of BA11 and BA9 were negatively correlated with HAMD and SDS score.…”
Section: Discussionsupporting
confidence: 93%
“…It cannot pass directly through the blood–brain barrier unless with the help of ryptophan and transporters. The decrease of 5‐HT level in peripheral blood can indirectly reflect the level of 5‐HT, which may be closely related to indoleamine 2,3‐dioxygenase 1 (IDO1) and metabolism of tryptophan 39 . Our results demonstrated that the level of 5‐HT in serum of MDD patients was significantly decreased, and the ReHo in BA11 and BA9 regions of PFC was decreased, which was consistent with the reported study 40 .…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation for the increased synthesis of serotonin in the TME is that inhibition of IDO1 may elevate Trp concentration systemically or locally and shunt catabolism toward the serotonin pathway. However, across 6 studies of EPA monotherapy and 22 studies of EPA in combination with other agents (a total of 2490 subjects), only four cases of suspected “serotonin syndrome” have been reported ( 35 ). Moreover, the effect of EPA on serotonin amounts in the brain extracellular fluid was minimal in rats ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, across 6 studies of EPA monotherapy and 22 studies of EPA in combination with other agents (a total of 2490 subjects), only four cases of suspected “serotonin syndrome” have been reported ( 35 ). Moreover, the effect of EPA on serotonin amounts in the brain extracellular fluid was minimal in rats ( 35 ). In the current study, we evaluated the impact of EPA on serotonin in the human TME.…”
Section: Discussionmentioning
confidence: 99%
“…This degrader was based on the IDO1 inhibitor epacadostat, a holo-IDO1 inhibitor, and displayed a DC 50 = 2.8 μM that is significantly weaker than the IDO1-PROTAC, NU223612 , described here. There was also no in vivo evidence of IDO1-PROTAC effects combined with the known inability for epacadostat to enter the brain . Herein, we report the development of an IDO1-PROTAC library utilizing the existing BMS-986205 ( NU223618 ) apo-IDO1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%